Book Review - Ofreneo, Rosalinda Pineda (Review of Women's Studies, 1991)
Book review of Fishers, Traders, Farmers, Wives - The Life Stories of Ten Women in a Fishing Village by Jeanne Frances I. Illo and Jaime B. Polo. Quezon City: Institute of Philippine Culture, Ateneo de Manila University, 1990.